Disaster in Itî's land the tragic social history of the Datû class in Leyte (1521-1622) - Borrinaga, Rolando O. (2010)
The label "Leyte" comes from Ila Itî, meaning it "belongs to Iti". It replaced the island's older name, Abuyo, and seems to have been intended to memorialize the tragic fate of the datû (indigenous elite) family that extended hospitality to the early Spanish explorers who reached our shores (the expeditions of Magellan, Villalobos and Legazpi). The family's descendants were exterminated in the wake of the Bankaw Revolt in 1621, a century after initial contact. This paper reconstructs the social history of the datû class in Leyte from the initial contact with the Magellan expedition in 1521, through the contacts with members of the Villalobos expedition in the 1540s and the Legazpi expedition in 1565. It will also look into their reactions to the early Spanish attempts to subjugate them, their accommodation of the new colonial order, and the price they paid for the loss of their old alliances with the Muslims in the south, until the tragic revolt in 1621. This paper also theorizes the demise of the seemingly ignored rajah class, the possible "royalty" in these islands, and their confederate territories within a century from the Spanish contact; expounds on the estuarine geography of the large settlements at that time (i.e., not only along the sea coasts or rivers); and clarifies key local jargon pertaining to Visayan settlements (i.e., lúngsod/ bóngto, gamurô, haúp, dolohan; definitely not barangay) and the social structure (i.e., orípun and its variants vs. the Tagalog and textbook alipin and its variants) as they applied to Leyte. A previously missed social class in the Visayas, the tumao (tumáwu), will also be introduced here.
Includes bibliographical references (pages 87-91).